Positive effect of shade and vermicompost application in the growth of pitahaya (Hylocereus ocamponis and Hylocereus undatus) - Castillo-González, Ana María; Hernández-Ramos, Lyzbeth; García-Mateos, María del Rosario; Ybarra-Moncada, Ma. Carmen; Nieto-Angel, Raúl (Journal of the Professional Association for Cactus Development, 2025)
Pitahaya (Hylocereus spp.) is a cactus of horticultural importance for its edible fruits. There is little information about the response of these plants to shading and fertilization conditions, which can limit pitahaya growth. The objective of this study was to evaluate the effect of shade (no shade, 35, and 50 % shade) and the application of vermicompost (0 and 3 kg) on plant growth, biochemical response and stem nutrient content in two species of pitahaya (Hylocereus ocamponis and H. undatus) grown in a greenhouse. The pitahaya cuttings were placed in 10 L pots with 12 kg of a mixture of mountain and leaf soil. The plants were maintained in a glass greenhouse under 12 different treatments, generated by the combination of three factors, species, shade, and fertilization based on vermicompost. The results showed that the total chlorophyll concentration of the stems was 23 % higher in plants grown under 35 % shade than in no shade. Hylocereus ocamponis had the highest growth and dry weight accumulation under 35 % shade, whereas Hylocereus undatus showed greater adaptability to cultivation under full sunlight and with 35 % shade. Hylocereus ocamponis was found to be more sensitive to high levels radiation. The nitrogen, Ca, Mg and Zn contents were 11, 21, 11 and 38 % lower in pitahaya stems grown under 50 % shade than in no shade. In general, vermicompost improved the contents of nutrients in the plants. The cultivation of two pitahaya species with 50 % shade is not recommended, given the lower accumulation of dry weight, growth and because of favors the etiolation.